Kárpátalja 1920–2020. A kárpátaljai magyarság elmúlt 100 éve - Csernicskó István; Черничко Степан; Csernicsko Istvan; Hires-László Kornélia; Гіреш-Ласлов Корнелія; Karmacsi Zoltán; Кормочі Золтан; Márku Anita; Марку Аніта; Máté Réka; Матей Рейка; Tóth-Orosz Enikő; et al. (Hodinka Antal Nyelvészeti Kutatóközpont, 2020)
Kiadványunk célja, hogy röviden bemutassa, hogyan alakult a ma Kárpátaljaként ismert régió történelmi, oktatási, gazdasági, nyelvi, vallási helyzete az 1920-as trianoni békediktátum után napjainkig.

Abstract. Transcarpathia, as a geographical-administrative unit, was created in 1919 as a result of peace treaties ending World War I, as a part of the (first) Czechoslovak Republic, under the name Podkarpatska Rus. A century ago, political decisions not only created the state of the Czechoslovak Republic, an administrative unit lacking historical background, but also the Hungarian national minority of Transcarpathia. During the 20th century, historical storms swept through what is now known as Transcarpathia: after the Hungarian Kingdom and within the Austro-Hungarian Monarchy, it belonged to Czechoslovakia, and during a transitional period, a part of its territory formed a short-lived state (Carpatho-Ukraine); for a short time it returned to the Kingdom of Hungary; it was annexed to the Soviet Union after another transitional period (Transcarpathian Ukraine); In 1991, it was inherited by Ukraine, which became independent at the time.
Transcarpathia 1920–2020. Transcarpathian Hungarians in the Last 100 Years
Keywords: Kárpátalja; 1920–2020; magyarság; történelem